On the Generation of Lyapunov Functions for Discrete-Data Systems - Nagaraja T.; Chalam V.V. (My University, 2025)
A previously reported method given by the present authors [1] is extended to discrete-data systems for the generation of Lyapunov functions. An example illustrates the systematic nature of the method. Copyright © 1977 by The Institute of Electrical and Electronics Engineers, Inc.